Population-based resistance of Mycobacterium tuberculosis isolates to pyrazinamide and fluoroquinolones: results from a multicountry surveillance project. Issue 10 (October 2016) - Zignol, Matteo; Dean, Anna S; Alikhanova, Natavan; Andres, Sönke; Cabibbe, Andrea Maurizio; Cirillo, Daniela Maria; Dadu, Andrei; Dreyer, Andries; Driesen, Michèle; Gilpin, Christopher; Hasan, Rumina; Hasan, Zahra; et al.
Summary: Background: Pyrazinamide and fluoroquinolones are essential antituberculosis drugs in new rifampicin-sparing regimens. However, little information about the extent of resistance to these drugs at the population level is available. Methods: In a molecular epidemiology analysis, we used population-based surveys from Azerbaijan, Bangladesh, Belarus, Pakistan, and South Africa to investigate resistance to pyrazinamide and fluoroquinolones among patients with tuberculosis. Resistance to pyrazinamide was assessed by gene sequencing with the detection of resistance-conferring mutations in the pncA gene, and susceptibility testing to fluoroquinolones was conducted using the MGIT system. Findings: Pyrazinamide resistance was assessed in 4972 patients. Levels of resistance varied substantially in the surveyed settings (3·0–42·1%). In all settings, pyrazinamide resistance was significantly associated with rifampicin resistance. Among 5015 patients who underwent susceptibility testing to fluoroquinolones, proportions of resistance ranged from 1·0–16·6% for ofloxacin, to 0·5–12·4% for levofloxacin, and 0·9–14·6% for moxifloxacin when tested at 0·5 μg/mL. High levels of ofloxacin resistance were detected in Pakistan. Resistance to moxifloxacin and gatifloxacin when tested at 2 μg/mL was low in all countries. Interpretation: Although pyrazinamide resistance was significantly associated with rifampicin resistance, this drug may still be effective in 19–63% of patients with rifampicin-resistant tuberculosis. Even though the high level of resistance to ofloxacin found in Pakistan is worrisome because it might be the expression of extensive and unregulated use of fluoroquinolones in some parts of Asia, the negligible levels of resistance to fourth-generation fluoroquinolones documented in all survey sites is an encouraging finding. Rational use of this class of antibiotics should therefore be ensured to preserve its effectiveness. Funding: Bill & Melinda Gates Foundation, United States Agency for International Development, Global Alliance for Tuberculosis Drug Development.